Spatial Variations of Commuting Behavior and Their Impact Factors in Shanghai Metropolitan Area - Li, Kaiming; Yue, Liying; Geng, Huizhi; Li, Kaishun (Frontiers in Built Environment, 2022)
Exploring the spatial variations (SV) and impact factors (IF) of commuting behavior is vital to promote cities' sustainable development and improve residents' daily lives. Based on 2015 1% Population Sample Survey data in Shanghai, this study constructs an improved accessibility index to evaluate the jobs-housing spatial relationship and compares SV and IF of commuting duration and commuting distance at the sub-district level by using spatial autocorrelation analysis, spatial lag model (SLM) and spatial error model (SEM). In terms of SV, the median commuting distance and commuting duration are 6.32 km and 28.37 min, respectively. Both of them have significant spatial autocorrelation, and the latter is higher. The high-high agglomeration areas of commuting distance scatter between the outer ring road and the outer suburbs. The high-high agglomeration areas of commuting duration are mainly distributed between the middle and outer ring roads. In terms of IF, the impacts of social factors on the commuting level are more significant than spatial factors. Ignoring the former will overestimate the effects of the latter. Commuting distance is more significantly correlated with spatial factors, and job accessibility is the most critical factor; while commuting duration is more significantly associated with social factors, education level is the essential factor. There is significant intra-urban heterogeneity and spatial autocorrelation of commuting distance and duration in the metropolis. Social factors are more influential than spatial factors on commuting behavior.